Abstracts of the 44th Annual Conference of Young Scientists ‘Cold in Biology and Medicine. Current Issues in Cryobiology, Transplantology and Biotechnology’ May 19, 2020, Kharkiv, Ukraine - Problems of Cryobiology; Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 280–282